2021
DOI: 10.3390/pr9111866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Passivator Synthesized by Wastes of Iron Tailings and Biomass on the Leachability of Cd/Pb and Safety of Pak Choi (Brassica chinensis L.) in Contaminated Soil

Abstract: Cadmium (Cd) and lead (Pb) carry a high heavy-metal-toxic risk for both animals and plants in soil. In this study, iron-based biochar (T-BC) was prepared by co-pyrolysis using wastes of iron tailings and biomass with urea as the functioning agents. Field-emission scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and toxicity-characteristic leaching procedure (TCLP) methods were employed to analyze the physicochemical characteristics of T-BC. Additionally, a pot trial was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…They also found that amaranth, as a dominant species, can effectively remove heavy metals from tailings. In another study by Zhou and Li [69] the preparation of ironbased biochar (T-BC) was explored as a means of soil remediation. They used iron tailings waste and biomass as raw materials and found that T-BC could adsorb and immobilize heavy metals in contaminated soil [70].…”
Section: Ecological Restoration and Reconstruction Of Ecosystem Funct...mentioning
confidence: 99%
“…They also found that amaranth, as a dominant species, can effectively remove heavy metals from tailings. In another study by Zhou and Li [69] the preparation of ironbased biochar (T-BC) was explored as a means of soil remediation. They used iron tailings waste and biomass as raw materials and found that T-BC could adsorb and immobilize heavy metals in contaminated soil [70].…”
Section: Ecological Restoration and Reconstruction Of Ecosystem Funct...mentioning
confidence: 99%
“…The preparation of iron‐based biochar by co‐pyrolysis of ITS and biomass improves soil pH, mineral nutrients and soil enzyme activity. [ 17 ] Cobalt ferrite nanoparticles were co‐precipitated from ITS and successfully applied in photo/sono‐catalytic degradation of Congo red. [ 18 ] A novel mesoporous silica material from ITS exhibited high absorbance capability for methylene blue because of the porous structure.…”
Section: Introductionmentioning
confidence: 99%